Realized niche modelling uncovers contrasting responses to fire according to species-specific biogeographical affinities of amphibian and reptile species. (26th November 2018) - Santos, Xavier; Sillero, Neftalí; Poitevin, Françoise; Cheylan, Marc
Abstract: The responses of animal communities to fire are not well understood. We used modelling techniques to analyse how fire altered the habitat suitability of amphibian and reptile species across a 37-year chronosequence (1975–2011). The study was conducted at a biogeographical crossroads between the Mediterranean and medio-European bioregions. Using 9449 georeferenced locations, we examined the temporal variation in species-specific relative abundance, and built realized niche models with Maxent. We compared the habitat suitability index of Maxent models between two distant periods with a large number of records (1987–1989 and 2009–2011), and separated by two years with high fire activity, 1990 and 2003. Generalized linear models were applied to check temporal variation in habitat suitability indexes between the two periods as well as biogeographical affinity. Fire-history variables contributed strongly to the realized niche models. Due to high fire activity in the study area, habitat suitability decreased between the 1987–1989 and 2009–2011 periods for non-Mediterranean species. In contrast, most Mediterranean species benefited as a result of the land-cover openness created by fire. Modelling techniques are a useful complement to fieldwork for examining patterns in species responses to fire at biogeographical crossroads. The biogeographical affinity of species predicts their responses to fire.